(untitled) (Bangladesh Veterinarian, 2010)
Sixty-eight cows in group A were fed 63.9 megajoules (MJ)/day, 66 in B were fed 52.9, and 66 in C were fed 51.1 MJ/day. The mean (± SD) services per pregnancy of cows in groups A, B and C were 1.7 ± 0.7, 1.9 ± 0.6 and 2.5 ± 0.9, respectively. The mean calving to 1stfirst service intervals were 158.1 ± 51.5, 171.0 ± 59.0 and 200.0 ± 50.3 days, respectively. The mean milk yields were 5.8 ± 2.6, 4.5 ± 1.9 and 4.3 ± 1.9 litres/ day, respectively. Pregnancy rate was significantly (P<0.05) affected by breed, parity, age, body condition score (BCS) and body weight of cows. Breed and parity had no significant effect on pregnancy rate. Age, BCS and body weight had significant (P<0.05) affect on pregnancy rate. (Bangl. vet. 2010. Vol. 27, No. 1, 8 – 17) DOI: 10.3329/bvet.v27i1.5910